Digital Surveillance and the Erosion of Communication Privacy : A Literature Review - Ilham Gemiharto; Samson CMS (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
The rapid proliferation of digital surveillance technologies has significantly transformed communication privacy in Southeast Asia, generating conflicts among state security priorities, corporate data practices, and civil liberties. This literature review integrates theoretical perspectives from Surveillance Studies (including surveillance capitalism and panopticism), Communication Privacy Management Theory, and Contextual Integrity, complemented by regional policy examinations and qualitative data from interviews with activists, journalists, and students in Indonesia, Singapore, and Malaysia. Emerging hybrid surveillance systems, encompassing social media monitoring, facial recognition, and spyware, are advanced by state entities and platforms such as Meta, Google, and ByteDance. Legislative frameworks, including Indonesia's UU ITE and PDP Law, Singapore's POFMA alongside cybersecurity measures, and Malaysia's CMA revisions, rationalize expansive monitoring for security and misinformation mitigation, though they permit mission creep with inadequate protections.​ These dynamics produce chilling effects, manifesting as self-censorship on social platforms, modified offline engagements, platform skepticism, and spiral-of-silence phenomena fueled by perceived oversight and fear-driven conformity. The central tension endures: surveillance ostensibly enhances safety and order but diminishes communicative independence, interpersonal trust, and democratic discourse in hybrid regimes. Preserving privacy necessitates robust GDPR-equivalent regulations, accountable oversight, and grassroots digital literacy initiatives. Keywords: digital surveillance, communication privacy, chilling effect, self-censorship, Southeast Asia.